A circular economy model for ethanol and alcohol-based hand sanitizer from sweet potato waste in the context of COVID-19 - Trevisan Weber, Caroline; Ranzan, Lucas; Menz Liesegang, Luciano Luís; Ferreira Trierweiler, Luciane; Trierweiler, Jorge Otávio (Brazilian Journal of Operations & Production Management, 2020)
Goal: The goal of the present work is to analyze the techno-economic viability of a biorefinery to generate ethanol and alcohol-based hand sanitizer from sweet potato waste within the concept of a circular economy. Design / Methodology / Approach: A survey of expenses for a 1000 L.day-1 distilled plant was carried out, and five different market scenarios were evaluated, varying the rate of production of each product. Results: Results show that the higher the production of the hand sanitizer, the more lucrative the scenarios are. The economic breakeven point occurs when the percentage of the alcohol-based hand sanitizer production is equal to 34%. However, the project becomes economically attractive from the production rate of 39%. The scenario for 80% of alcohol-based hand sanitizer production resulted in NPV of US 913,140.92, IRR of 64%, with a discounted payback of 0.72 year. Limitations of the investigation: It was considered that all the production was sold, which is in line with the current market demand. However, if the market slows down, the sales and the revenue obtained may be lower. Practical implications: The production of hand sanitizer from sweet potato waste is an opportunity to meet the market needs in scenarios such as the COVID-19 pandemic. Besides, the proposed biorefinery promotes the development of the circular economy through waste minimization. Originality / Value: No studies about the production of ethanol and alcohol-based hand sanitizer from sweet potato waste in an integrated way, and the simulation of different real market scenarios were found.